Correlation of Neutrophil Lymphocyte ratio with HbA1c in patients of type 2 Diabetes Mellitus attending Medical Department of a Tertiary Care Centre - Singh, R; Shrestha, JK; Chaudhary, OP; Singh, S; Agrahari, MK (Journal of Diabetes and Endocrinology Association of Nepal, 2023)
Background: Type 2 diabetes mellitus is associated with chronic low-grade inflammation. Neutrophil lymphocyte is an indicator of subclinical inflammation. One of the novel inflammatory markers is neutrophil to lymphocyte ratio. We find only less studies that are directly accessing the relation between NLR and HbA1c, in the present study we aim to correlate neutrophil lymphocyte ratio with glycemic control in patients having type 2 diabetes.Methods: Hospital based observational cross section study was carried out at department of medicine at Bharatpur Period August 2023 to December 2023. 176 patients with type 2 diabetes mellitus as per ADA criteria aged more than 18 years were included in the study. Microsoft excel and SPSS version 20.0 were used for collection and analysis of the data, p